Adaption of Roots to Nitrogen Deficiency Revealed by 3D Quantification and Proteomic Analysis. Issue 1 (19th November 2018) - Qin, Lu; Walk, Thomas C.; Han, Peipei; Chen, Liyu; Zhang, Sheng; Li, Yinshui; Hu, Xiaojia; Xie, Lihua; Yang, Yong; Liu, Jiping; Lu, Xing; Yu, Changbing; et al.
Abstract : Proteomics analysis reveals the mechanisms underlying root architectural changes in response to N deficiency. Abstract: Rapeseed ( Brassica napus ) is an important oil crop worldwide. However, severe inhibition of rapeseed production often occurs in the field due to nitrogen (N) deficiency. The root system is the main organ to acquire N for plant growth, but little is known about the mechanisms underlying rapeseed root adaptions to N deficiency. Here, dynamic changes in root architectural traits of N-deficient rapeseed plants were evaluated by 3D in situ quantification. Root proteome responses to N deficiency were analyzed by the tandem mass tag-based proteomics method, and related proteins were characterized further. Under N deficiency, rapeseed roots become longer, with denser cells in the meristematic zone and larger cells in the elongation zone of root tips, and also become softer with reduced solidity. A total of 171 and 755 differentially expressed proteins were identified in short- and long-term N-deficient roots, respectively. The abundance of proteins involved in cell wall organization or biogenesis was highly enhanced, but most identified peroxidases were reduced in the N-deficient roots. Notably, peroxidase activities also were decreased, which might promote root elongation while lowering the solidity of N-deficient roots. These results were consistent with the cell wall components measured in the N-deficient roots. Further functional analysis using transgenic Arabidopsis ( Arabidopsis thaliana ) plants demonstrated that the two root-related differentially expressed proteins contribute to the enhanced root growth under N deficiency conditions. These results provide insights into the global changes of rapeseed root responses to N deficiency and may facilitate the development of rapeseed cultivars with high N use efficiency through root-based genetic improvements.